Development of Culture-Based Learning Through Children’s Kerinci Folk Stories in Kindergarten - Latifa, Baiti; Suryana, Dadan; Mayar, Farida; Mahyuddin, Nenny (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Introduction to regional culture needs to be introduced from an early age through education. One form of instilling cultural values in schools is through culture-based learning. This research aims to develop culture-based learning through Kerinci folklore in kindergartens. The type of research used is Research and Development with the Born & Gall Design Model. The subjects of this research consisted of 20 children at the Pembina Pondok Tinggi State Kindergarten, Sungai Full City. Development of culture-based learning through Kerinci folklore at the Pembina Pondok Tinggi State Kindergarten seen in terms of learning activities and children's learning outcomes. From the aspect of learning activities during the implementation of learning, children are enthusiastic in listening, responding and carrying out evaluations. The results of children's development as seen from the observation sheet on six aspects of child development show that the children's scores during the pre-test and post-test have all increased, meaning that culture-based learning is effective to use and apply in learning. So, that the expected development according to the child's age can be achieved well and maximum.